Faktor hubungan dengan kejadian stunting di Puskesmas Tamalate Kota Makassar - Dewi Purnama Windasari; Ilham Syam; Lilis Sarifa Kamal (AcTion: Aceh Nutrition Journal, 2020)
Stunting is a chronic condition of stunted growth due to long-term malnutrition and manifestations. In Indonesia, since 2017, toddlers stunted by 29,6%, and in 2018 increased to 30,8%. This study aims to determine the relationship of infectious diseases, initiation of early breastfeeding, history of exclusive breastfeeding, LBW, and first marriage with stunting. The method used in this study was observational analytic with a cross-sectional study approach, with a chi-square test and fisher's exact test population of 620 people, with a sample of 124 toddlers with purposive sampling technique. The results showed that there was a relationship between early breastfeeding initiation (p=0,014) exclusive breastfeeding (p=0,001), and was not the relationship between LBW (p=0,172) with the occurrence of stunting in the Tamalate Community Health Center in Makassar. In conclusion, there is no correlation between infectious disease and LBW with the incidence of stunting, and there is a relationship between early breastfeeding, exclusive breastfeeding, with stunting. It is recommended to mothers to maintain the child's lifestyle and diet to avoid infectious diseases, give children early breastfeeding and exclusive breastfeeding, also reject early marriage so as not to give birth to a child with LBW and cause stunting. Stunting merupakan kondisi kronis terhambatnya pertumbuhan karena malnutrisi jangka Panjang dan manifestasi, di indonesia tahun 2017 terdapat 29,6% balita yang mengalami stunting dan tahun 2018 terdapat 30,8% balita yang mengalami stunting. Penelitian ini bertujuan untuk mengetahui hubungan penyakit infeksi,inisiasi menyusui dini, riwayat asi eksklusif, BBLR dan pernikahan dini dengan kejadian stunting. Metode yang digunakan pada penelitian ini adalah observasional analitik dengan pendekatan cross-sectional study, dengan uji chi-square dan uji fisher’s exact test   populasi sebanyak 620, dengan sampel sebanyak 124 balita dengan teknik  purposive sampling. Hasil penelitian menunjukan bahwa ada hubungan antara IMD (p= 0,014) ASI esklusif (p= 0,001), dan tidak terdapat hubungan antara BBLR (p= 0,172) dengan kejadian stunting di Wilayah Kerja Puskesmas Tamalate kota Makassar. Simpulan, tidak terdapat hubungan riwayat penyakit infeksi dan BBLR dengan kejadian stunting, ada hubungan antara IMD, ASI eksklusif, dengan kejadian stunting. Saran, untuk menjaga pola hidup dan pola makan anak agar terhindar dari penyakit infeksi, memberi anak IMD dan ASI eksklusif, juga menolak pernikahan dini agar tidak melahirkan anak yang BBLR dan menyebabkan stunting.